The association between Saudi football clubs and the loyalty of their fanbase, a cross-sectional study. (International Journal of Scientific Research and Management (IJSRM), 2022)
This cross-sectional study analyzes the association between Saudi football clubs and the loyalty of their fanbase and evaluates how the fans are acting as consumers toward their football clubs. Data was collected through a questionnaire. The research was carried out on a sample of 2,317 participants. The findings show that more than half of participants have attended a football match in the Saudi football league whereas 23.7% preferred to watch their favorite team in the stadium. Furthermore, the loyalty of the fans can also be evaluated by the purchases of the club related products as the participants majority own their favorite club shirts where almost half of them have purchased another club’s products. The limitations of the study that it is focused on limited behaviors of the fans and further investigations can be achieved to include what are the factors preventing the fans from being loyal to their football clubs or why they are not attending to the stadiums although they have showed the intention to.